La concepción, lanzamiento y desarrollo de la empresa Beats, una plataforma virtual de creación de canciones personalizadas. - Ruiz Muñoz, Diana Verónica (2021)
The main objective of this work is the development of an innovative business idea, through an analysis of the current dynamics of the music market and the rise of the digital age. By means of the new consumption channels that have been created under this juncture, an environment conducive to the development of start-ups has been created that place personalization at the first levels of relevance within its audience. This perfect storm, adjacent to the principles of personalization of the sono-sphere and, the characteristics of the millennial generation (one of the captive audiences of this digital transformation), allow and make viable the creation of the BEATS project: a start-up of personalized music that works through a web platform. In it, the user can become a musical co-author of their own song, and it will tell their story. Through the use of digital analysis tools, together with a plan of communication strategies and tactics, it has been possible to take clear advantage of the dynamic capabilities of a business idea, which has been raised in a competitive environment and has achieved important results.